2013
DOI: 10.4149/bll_2013_123
|View full text |Cite
|
Sign up to set email alerts
|

Growth and obesity and its association with plasma level of steroid hormones and insulin-like growth factor-I (IGF-I) in Slovak female students

Abstract: Abstract:The aim of the present study was to examine the possible role of steroid hormones and insulin-like growth factor 1 (IGF-I) in the control of human growth and obesity. We measured plasma level of progesterone, testosterone, estradiol and IGF-I in 301 young women at different stages of their ovarian cycle, and compared them to the standard morphometric indexes of their growth and obesity -body height, body weight, abdomen circumstance and waist to hip ratio (WHR). The ovarian cycle-dependent changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Oestradiol is produced by the granulosa cells of the follicles during reproductive years, and the effect of obesity on its synthesis is controversial. Some authors have described obese women showing higher oestradiol concentrations than normal-weight patients (Zatko et al, 2013) while others have found that obese patients have lower oestradiol concentrations (Rehman et al, 2012;Rochester et al, 2009;Ross et al, 2014;Santoro et al, 2004), with a possible direct inhibitory effect of body mass on gonadotrophin and oestradiol production (De Pergola et al, 2006). In agreement with these latter findings, in this study it was found that obese CAF-fed animals showed decreased serum oestradiol concentrations.…”
Section: Discussionsupporting
confidence: 86%
“…Oestradiol is produced by the granulosa cells of the follicles during reproductive years, and the effect of obesity on its synthesis is controversial. Some authors have described obese women showing higher oestradiol concentrations than normal-weight patients (Zatko et al, 2013) while others have found that obese patients have lower oestradiol concentrations (Rehman et al, 2012;Rochester et al, 2009;Ross et al, 2014;Santoro et al, 2004), with a possible direct inhibitory effect of body mass on gonadotrophin and oestradiol production (De Pergola et al, 2006). In agreement with these latter findings, in this study it was found that obese CAF-fed animals showed decreased serum oestradiol concentrations.…”
Section: Discussionsupporting
confidence: 86%
“…) (Flier and Maratos-Flier, 2005;Lovejoy, 1998;Markova et al, 2014). Among these factors the literature highlights the role of sex hormones and their physiological fluctuations during the female reproductive cycle (Lovejoy, 1998;Zatko et al, 2013). The women who perform outdoor duties are exposed to several substances present in the urban pollution which may interfere with the normal levels of hormones, as suggested by some of our studies (Caciari et al, 2013;Ciarrocca et al, 2006Ciarrocca et al, , 2011Monti et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…These measurements are based on subjective evaluation in scales/inventories completed by tested individuals or on rankings provided by caregivers/parents (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In our pilot study we used specifi c method for assessments of aggressive behavior-functional behavioral assessment based on principles of applied behavioral analysis (ABA) (31).…”
Section: Discussionmentioning
confidence: 99%
“…The literature also suggests that testosterone may be involved in the etiology of aggression in humans as another contributing biological factor. Testosterone is a male sex hormone, but in fact, it regulates sexual arousal and many other processes in both genders (13). Several studies have examined the relationship between salivary/plasmatic testosterone levels and aggression in various populations with mixed results.…”
Section: Introductionmentioning
confidence: 99%